Design and development of an uncertainty situation in kindergarten (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this piece of work, we show the design and develop of a teaching experience about the uncertainty in a class with children aged 5-6 years old. The experience is based on the resolution of probability problems by simulation, and has as main aim to evaluate to what extend it is possible to tackle and solve probability problems by this way in a K-grade class. The experience is developed through three phases. In the first, the teacher introduces the situation; in the second everyone student carries out a simulation of the problem and gives an answer; and in the third, the teacher puts together all information provided by students. Based on what we observed, we conclude that tasks like this we are proposing in this article is possible in a 5-6 years old class, very empty of this type of contents. We suggest that more research and experimentation is required.
Keywords: Early Childhood Education; Mathematics Education; Uncertainty situations; Problem solving; Probability; Simulation